Wettability and Cell Viability in Uncoated Titanium Alloys - Renato Trevilato; Kelli Cristina Micocci; Débora Carneiro Moreira; Carlos Eiji Hirata Ventura; Armando Ítalo Sette Antonialli (Materials Research)
The biological response to metallic biomaterials is strongly influenced by surface properties such as topography and wettability. This study evaluated the influence of roughness and contact angle on the cellular viability of pre-osteoblasts (MC3T3-E1) cultured on commercially pure titanium (grade 4), Ti-6Al-4V ELI, and Ti-12Mo-6Zr-2Fe (TMZF) alloy. Samples were machined by facing on a lathe using fixed parameters without coolant, and subsequently polished and characterized by confocal microscopy. Wettability tests were performed using the sessile drop method with varying droplet volumes and fitting methods using an optical tensiometer. Biological assays were conducted at 24, 48, and 72 hours using resazurin. Results showed that the combination of arithmetic roughness (0.6 and 1.3 µm) and hydrophilic behavior enhanced cell adhesion and proliferation, particularly on the TMZF alloy. Topographic symmetry (Rsk) and kurtosis (Rku) were more strongly correlated with biological response than mean roughness (Ra). The findings suggest that surface features and wettability properties act synergistically to modulate cell behavior and play a key role for biocompatibility and the development of optimized surfaces for biomedical applications.